Construire la paix au Guatemala: analyse critique des modalités d'intervention mises en œuvre par trois ONG guatémaltèques - Vanthuyne, Karine (Anthropologica, 2022)
Based on a study conducted within three NGOs involved in the Guatemalan peace process, this article interrogates dominant discourses and practices upon which strategies of reconciliation in postwar countries are based. Examining local idioms of the reconstruction of the principle of "living together," and in particular the moral and political economy in which these idioms are embedded and the discursive fields to which they refer, enables us to identify the obstacles that a repressive political context may impose on processes of peace building and reconciliation